2020
DOI: 10.1101/2020.05.28.121137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overlapping connectivity gradients in the anterior temporal lobe underlie semantic cognition

Abstract: Convergent evidence from neuroimaging, computational, and clinical research has shown that the anterior temporal lobe (ATL) is critically involved in two key aspects of semantic cognition: the representation of semantic knowledge, and the executive regulation of this knowledge. Both are necessary for integrating features to understand concepts, and to integrate concepts to understand discourse. Here, we tested the hypothesis that these differential aspects of integration map onto different patterns of ATL conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Accumulating evidence suggests that the organization of the isocortex 8,22,23,25,[61][62][63][64][65] , the cerebellum 38,39 , and the hippocampus 7,40-42,66 can be described with multiple gradients of functional features that map onto structural features in the human brain. In the present study, analyses of two large datasets (N > 2000) replicated two gradients identified by published research describing cerebellar and hippocampal functional connectivity to the isocortex 38,42 , and additionally revealed the topography of the third gradient in each structure that, to our knowledge, has not previously reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that the organization of the isocortex 8,22,23,25,[61][62][63][64][65] , the cerebellum 38,39 , and the hippocampus 7,40-42,66 can be described with multiple gradients of functional features that map onto structural features in the human brain. In the present study, analyses of two large datasets (N > 2000) replicated two gradients identified by published research describing cerebellar and hippocampal functional connectivity to the isocortex 38,42 , and additionally revealed the topography of the third gradient in each structure that, to our knowledge, has not previously reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence reveals that the organization of the cerebral cortex 30,[32][33][34][35][36][64][65][66] , the cerebellum 38,59 , and the hippocampus 39-41,67,68 can be described with multiple gradients of structural and functional features in humans. In the cerebral cortex, converging evidence from network-, circuit-, and cytoarchitectural-levels of analysis suggest that such gradients can be interpreted as the organizing principles underlying predictive processing 36,55,56,69,70 , guiding the flow of prediction signals, prediction error signals, and precision signals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work indicates that these dimensions reflect gradients of continuous spatial variation in regional functional connectivity ( Haak et al, 2018 ; Margulies et al, 2016 ; Zhang et al, 2019 ) and cytoarchitecture ( Burt et al, 2018 ; Paquola et al, 2019 ; Wang, 2020 ). These gradients capture both the major sensorimotor-to-association axis of cortical organization ( Sydnor et al, 2021 ) and finer-grained delineations between subregions supporting distinct cognitive processes like in the anterior temporal lobe ( Faber et al, 2020 ). While gradients appear to reflect regional heterogeneity in circuit properties that sculpt brain activity dynamics ( Kong et al, 2021 ), it remains unclear how spatially fixed functional gradients can dynamically coordinate to generate distinct brain activity states.…”
Section: Introductionmentioning
confidence: 99%